(untitled) (Research, Society and Development, 2023)
The present case study proposed in this article uses a questionnaire answered by basic education teachers through the electronic platform (Survey Monkey). The data were collected through the research “School inclusion in times of pandemic” developed through a partnership between the FCC (Fundação Carlos Chagas), UFABC (Federal University of ABC), UFES (Federal University of Espírito Santo) and USP (University de São Paulo) in July 2020. Therefore, for our study, a survey of the responses to this questionnaire was carried out, and then a statistical analysis of the results was carried out, as well as their discussion. Thus, the present research allowed reflecting on the main challenges of teachers in remote teaching and their practices in the context of the pandemic and the suspension of face-to-face classes in the inclusive perspective.